Effect of biofermentation with taxifolin on physicochemical and microbiological properties of cold-smoked pork sausages - Gustiene, Sonata (Array, 2019)
The aim of this work is to evaluate the effect of taxifolin on the physicochemical and microbiological properties of cold-smoked pork sausages produced using different commercial starter cultures with Leuconostoc carnosum and with a mixture of Pediococcus pentosaceus and Staphylococcus xylosus. Ultra performance liquid chromatography analysis demonstrated that after 181 days of storage total taxifolin content was the highest in samples with taxifolin and L. carnosum (60 %), compared to the first day of storage. The sausages with taxifolin and the mixture of P. pentosaceus and S. xylosus (56 %) followed next. Taxifolin improved the hygienic quality of sausages without significant effect on the growth of lactic acid bacteria. The accumulation of biogenic amines, including histamine and putrescine, was more effectively reduced in sausages inoculated with the taxifolin and P. pentosaceus and S. xylosus mixture. Using this mixture, the rate of lipolysis and lipid oxidation were effectively slowed down.